Key dimensions affecting employees’ loyalty in oil and gas company / Anis Jusoh and M. Irsyaduddin A. Latif - Jusoh, Anis; A. Latif, M. Irsyaduddin (2016)
This research had studied on the corporate culture for Oil and Gas Company, also referred as Organizational Culture. Two companies had been selected, a plant for gas processing and another one is a plant for crude oil refinery, as to represent the population in the East Coast Region for the analysis. It is a system of shared actions, values and beliefs that develops within an organization and guides the behaviour of its members. Each organization in Oil and Gas Company has its own unique culture with some common cultural elements that yield stability and meaning for the organizations. It is believe that some cultural elements can have a major impact on the performance of the organizations and the quality of work life experienced by the members within the company.